Complementarity in Employee Participation Systems - Gabriel Burdin; Takao Kato (Global Labor Organization (GLO), 2021)
This chapter describes the nature, scope and effects of various non-mandated participatory work practices in Japan, the U.S. and Europe through the lens of organizational complementarity theory. Specifically, rather than being treated in isolation, each work practice is considered an element of HIWS (High Involvement Work System), an employment system comprised of clusters of complementary work practices. In so doing, the chapter provides a complete picture of nonmandatory participatory work practices. Furthermore, by applying the common framework of viewing participatory work practices as complementary elements of HIWS to seemingly disparate forms of work practices in different parts of the world, the chapter sheds light on how participatory work practices play out in diverse institutional, cultural and regulatory environments.
Keywords: M5; J5; 330; High Involvement Work System; High Performance Work System; Organizational Complementarities; Employee Participation